Catfish Extract-Based Shredded Meat as a Functional Food: Nutritional Composition, Safety, and Acceptance Among Mothers of Toddlers - Ferdinan Sihombing; Ellen Stephanie Rumaseuw; Maria Alfa Raniadita; Carissa Wityadarda (Jurnal Penelitian Pendidikan IPA, 2026)
Stunting is a chronic nutritional problem that has serious implications for the quality of human resources in Indonesia. One potential solution is the development of affordable local food innovations based on animal protein sources, such as catfish (Clarias batrachus), which has high nutritional value and can be processed into functional food products, including extracts and shredded fish (abon). This study aimed to analyze the nutritional composition, antioxidant activity, microbiological and heavy metal safety, as well as the organoleptic acceptance of shredded catfish products based on catfish extract among mothers of under-five children. The study was conducted at the Central Laboratory of Universitas Padjadjaran and the “Bina Harapan X” Integrated Health Post (Posyandu) in Cipeundeuy Village, West Bandung. Proximate analysis was performed on both catfish extract and shredded catfish products. Antioxidant activity was assessed using the DPPH method, while safety evaluations included Escherichia coli (CFU/mL) analysis and determination of lead (Pb) and cadmium (Cd) levels using Atomic Absorption Spectrophotometry (AAS). Organoleptic testing was carried out with 31 mother panelists who had under-five children, using a 5-point hedonic scale. The catfish extract contained 4.97% moisture, 8.91% ash, 29.87% fat, 48.85% protein, and 7.40% carbohydrates, with a total polyphenol content of 0.12% and an IC₅₀ value of 4.9724%. The shredded catfish product contained 3.32% moisture, 6.55% ash, 30.45% fat, 38.33% protein, and 21.36% carbohydrates. Safety analysis showed E. coli levels of 0 CFU/mL (safe for consumption), Pb levels of 0.3999 mg/kg, and Cd levels of 0.0312 mg/kg. Organoleptic scores for color (3.87), texture (3.97), and aroma (4.00) indicated an overall acceptance level of “liked”. Shredded catfish products based on catfish extract have high nutritional value, are safe for consumption, and are well accepted by mothers of under-five children. This product has strong potential as a local fish-based functional food to support stunting prevention efforts in the community